Observation of D0 meson decays to π+π−μ+μ− and K+K−μ+μ− final states - Aaij, R; Adeva, B; Adinolfi, M; Bjørn, M; Evans, T; Gandini, P; Cazon, BR; Hadavizadeh, T; Hancock, TH; Harnew, N; Hill, D; Jalocha, PG; et al. (American Physical Society, 2017)
The first observation of the D0→π+π−μ+μ− and D0→K+K−μ+μ− decays is reported using a sample of proton-proton collisions collected by LHCb at a center-of-mass energy of 8 TeV, and corresponding to 2  fb^−1 of integrated luminosity. The corresponding branching fractions are measured using as normalization the decay D0→K−π+[μ+μ−]ρ0/ω, where the two muons are consistent with coming from the decay of a ρ0 or ω meson. The results are B(D0→π+π−μ+μ−)=(9.64±0.48±0.51±0.97)×10^−7 and B(D0→K+K−μ+μ−)=(1.54±0.27±0.09±0.16)×10^−7, where the uncertainties are statistical, systematic, and due to the limited knowledge of the normalization branching fraction. The dependence of the branching fraction on the dimuon mass is also investigated.